Car Spare Parts Business Website Implementation Using Extreme Programming Approach And Its Effectiveness Analysis Based On Businessman Perspective - Jason Hirawan; Hendi Sama (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The growth of technology and the internet makes business owners begin to change their conventional ways. Utilizing websites to assist in business management is one of these trends. The industry that is growing at this time is the automotive industry, specifically the sale of replacement components., therefore this website was created to help the sale of replacement components business owners in managing their businesses. research method used in making the website is extreme programming using the native PHP programming language. The result of this development is a website that helps manage the sale of replacement components business, the test methods include validity, reliability, and effectiveness.